The significance of culture and cultural factors in New Zealand criminal law : a multicultural approach to criminality and culpability : a thesis submitted in fulfilment of the requirements for a Doctor of Philosophy at Te Kunenga Ki Pūrehuroa, Massey University, Palmerston North, New Zealand - Iosefa, Leuatea (Massey University, 2020)
The principal aim of the thesis is to provide a secure foundation for the need to define culture and to contribute to the development of a workable definition of culture and cultural factors for application in criminal law. A recalibration of the criminal law's approach to culture and cultural factors is necessitated by the unprecedented demands of a super-diversification of New Zealand's population; to bring together the currently disparate elements of culture that abound within criminal law and to address the cultural deficiencies that pervade criminal law. Because culture and cultural factors impact people in differing ways, the criminal law cannot therefore assume that all individuals will respond to specific situations in similar ways. Culture is an essential consideration within criminal law due to its significance and relevance to the determination of fundamental elements of offences and defences, however, New Zealand's substantive criminal law harbours numerous intrinsic characteristics that provide unique challenges to the recognition and application of culture. The substantive criminal laws implicitly requires the recognition of culture and cultural factors, however, the criminal law statutes make no express reference to culture nor provides a framework or guidelines for the interpretation and application of culture in criminal law. The criminal courts are therefore left to deal with culture in an ad hoc manner prompting claims of inequality of treatment, unfairness and inconsistency in the determination of cultural assertions. A clear delineation of "culture" and "cultural factors" will address the cultural deficiencies that permeate criminal law and also promote the development, by Parliament and the criminal courts, of a methodology for more meaningful recognition of culture.
Keywords: Criminal law; Social aspects; Cultural pluralism; Culture and law; New Zealand; 480401 Criminal law; 470212 Multicultural, intercultural and cross-cultural studies